2004
DOI: 10.1242/jeb.01050
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of energetic functioning and production of reactive oxygen species by lugworm (Arenicola marina)mitochondria exposed to acute temperature changes

Abstract: SUMMARY The influence of seasonal and acute temperature changes on mitochondrial functions were studied in isolated mitochondria of the eurythermal lugworm Arenicola marina (Polychaeta), with special emphasis on the interdependence of membrane potential and radical production. Acclimatisation of lugworms to pre-spawning/summer conditions is associated with rising mitochondrial substrate oxidation rates, higher proton leakage rates, elevated membrane potentials, and increased production of reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 31 publications
5
47
0
2
Order By: Relevance
“…The resulting ROS exceed primary scavenging capacity of an organism and attack different cellular components, such as nucleic acids, cytoplasmic proteins, lipids, and membranes (Dröge, 2002;Valavanidis et al, 2006). ROS production in cells, especially in the mitochondria and peroxisome, has been found to be increased in exercised mammalian muscle, stressed bivalve gills, chicken muscles, lugworm and cultured cells as compared with non-stressed control tissue (Keller et al, 2004;Heise et al, 2003). Increase in oxidative process during high concentration of heavy metal or any other pollution related stress causes ROS accumulation, and cellular protection against such damage is achieved mainly by enzymes such as SOD, CAT, GPx or GRd (Lin et al, 2015;Das et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting ROS exceed primary scavenging capacity of an organism and attack different cellular components, such as nucleic acids, cytoplasmic proteins, lipids, and membranes (Dröge, 2002;Valavanidis et al, 2006). ROS production in cells, especially in the mitochondria and peroxisome, has been found to be increased in exercised mammalian muscle, stressed bivalve gills, chicken muscles, lugworm and cultured cells as compared with non-stressed control tissue (Keller et al, 2004;Heise et al, 2003). Increase in oxidative process during high concentration of heavy metal or any other pollution related stress causes ROS accumulation, and cellular protection against such damage is achieved mainly by enzymes such as SOD, CAT, GPx or GRd (Lin et al, 2015;Das et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the H 2 O 2 generation rate of Aequipecten opercularis mitochondria were performed with a Shimadzu (RF-1501) fluorometer at the Port Erin Marine Laboratory, as described in detail by Philipp et al (2005b) for Laternula elliptica. Both H 2 O 2 generation rates and oxygen consumption rates were measured in parallel and related to mitochondrial protein content (for details see Keller et al 2004).…”
Section: Sampling and Maintenance Aequipecten Opercularismentioning
confidence: 99%
“…The increase in ROS reflects increased level of thermal stress. Keller et al, (2004) also observed that exposure of animals to elevated temperatures accelerated mitochondrial respiration and increased mitochondrial ROS formation. ROS, being cellular toxicants (Davidson et al, 1996), can be induced through hyperthermia (Flanagan et al, 1998).…”
Section: Oxidative Stress and Thermal Stressmentioning
confidence: 85%